Constitutional Law: Implikasi Bentuk Negara, Bentuk Pemerintahan dan Sistem Pemerintahan Terhadap Sistem Bernegara Lithuania - Yunus, Nur Rohim (UIN Jakarta, 2021)
There is a mixed system of governance in the Republic of Lithuania, which is a unitary republic located in the northeastern part of Europe. The system is mainly influenced by parliament. The prime minister and his cabinet hold the primary executive power in this system, while the Seimas, which corresponds to the national parliament, are the ones who hold the legislative power. In spite of the fact that there is a president who serves as the head of state, the president's powers are more restricted than in other presidential systems, with the primary emphasis being placed on matters pertinent to defense and foreign policy. A commitment to democratic values, integration with Western countries, and efforts to promote national identity and maintain the cultural legacy of the country are all emphasized by the method of government that is utilized in Lithuania.